VEGETATIVE PROPAGATION OF PATCHOULI BY CUTTING - BETTONI, Marcelle Michelotti; STORCK, Rafaellen Caroline; PEÑUELA, Lury Forero; MORAES, Carla Pedroso de (Scientia Agraria, 2010)
The patchouli is an aromatic species widely used by the cosmetic and perfume industry. The vegetative propagation of patchouli has been shown to be feasible by the technique of cutting. This study was conducted at the Federal University of Parana, Curitiba - PR, Brazil, under greenhouse condition with a system with intermittent irrigation during the months of May to July 2009. The experimental design was completely randomized consists of 6 treatments (cuttings with 1 pair of leaves, 1 pair of leaves halved, 1 leaf, 1 leaf reduced by half, without cutting leaves and leaf cuttings) with 4 replicates and 10 cuttings per plot. Cuttings were made with 6 cm in length, without application of plant growth regulators and were evaluated after 60 days. Cuttings with leaves showed higher rooting independent of leaf area maintained. The maintenance of 1 pair of leaves, whole or halved resulted in greater percentage and number of roots. The use of leaf cuttings and cuttings without leaves resulted in lower rooting and higher percentage of dead cuttings.